Strengthening Crop Breeding Networks and Partnerships in Sub Saharan Africa: Results of Three Years of Sustained Effort by CGIAR Accelerated Breeding Initiative - Das, Biswanath; Asea, Godfrey; Ndoye, Ousmane; Chataika, Barthlomew; Ilakut, Ben; Bänziger, Marianne; Quinn, Michael (CGIAR System Organization, 2024)
The primary objective of CGIAR Accelerated Breeding Initiative (ABI) has been to deliver higher rates of genetic gain and decrease the average age of varieties on farmers’ fields in the Low- and Mid-Income Countries (LMICs). A core requirement to achieve this ambitious objective is to establish strong partnerships, particularly with research and scaling partners working at regional, national and local levels. As a result, one of the primary outcomes targeted by Accelerated Breeding has been to ensure that 80% of targeted breeding networks have implemented documented steps towards stronger partnership models where National Agricultural Research and Extension Systems (NARES) and Small and Medium Enterprises (SMEs) have increased their breeding capacity and are providing greater scientific, operational and decision-making contribution to the breeding process. Here, we describe the efforts pursued by the Accelerated Breeding TRANSFORM Work Package between 2022 and 2024 to strengthen partnerships between CGIAR and national partners, with a particular focus on sub-Saharan Africa (SSA).